PRE-HOSPITAL MANAGEMENT OF SPINAL INJURIES IN A NATURAL DISASTER - Lodhi, Athar; Khan, Shahbaz Ali; Ahmed, Ehtisham; Fatima, Sadia; Fatima, Fozia; Pasha, Tousif; Alvi, Hamid Fazeel (Journal of Ayub Medical College Abbottabad, 2011)
Background: Spinal injuries are one of the most devastating and crippling conditions known to mankind. Natural calamities follow no rules, and all have the potential of devastating medical and public health resources, earthquakes being the deadliest. The incidence of spinal injuries increases by leaps and bounds in such calamities. Improper pre-hospital management and inadvertent manipulation of the spine during rescue and transfer can aggravate the damage. This study was conducted in order to access the level of pre-hospital care that had been provided to the patients with spinal injuries reaching Ayub Teaching Hospital, Abbottabad after the October 2005 earthquake. Methods: This study was conducted in the department of Neurosurgery, Ayub Medical College after the earthquake of October 2005. All patients sustaining spinal injuries were included in the study. Demographic data like age, gender and time of arrival at hospital were recorded. The important aspects of pre-hospital care like spinal immobilisation, intravenous access, fluid resuscitation, catheterisation, pain killers and intravenous steroids administration were also recorded. Results: Out of the 83 patients with spinal injuries, 55 (66.26%) were females and 28 (33.7%) were males. Age ranged from 12-68 years (mean 26.6±13.2 years). At the time of presentation 70 (84.3%) patients had complete spinal injury whereas 13 (15.6%) had incomplete spinal injury. Sixty-one (73.5%) patients were paraplegic and 22 (26.5%) cases were quadriplegic. Only 8 (9.6%) patients were brought to the hospital after proper spinal immobilisation on the spinal boards. Intravenous line was maintained in 24 (28.9%) patients and only 18 (21.7%) received some sort of fluid resuscitation. Thirty-eight (45.7%) were catheterised, 18 (21.6%) received some sort of parenteral analgesics and 4 (4.8%) received steroids at the time of patients. Only 10 (12%) were brought in properly equipped ambulances. Conclusion: Poor pre-hospital management of spinal injured patients depicts the lack of emergency preparedness as well as the lack of basic knowledge rescue teams and health care providers about the common trauma management measures. There is a dire need of educating rescue workers and volunteers about spinal injury in order to save lives minimise the secondary damage to already affected spine. Keywords: Spinal injury, pre-hospital management, earthquake 2005, spine immobilisation